Antidiabetic activity of ethanolic extract of tubers of Dioscorea alata in alloxan induced diabetic rats - Maithili, V. (Medknow Publications, 2011)
OBJECTIVE: To evaluate the antidiabetic activity of ethanolic extract of Dioscorea alata in glucose loaded and alloxan induced diabetic rats. MATERIALS AND METHODS: The authenticated tubers of D. alata (DA) (JSSCPDP/2008/157) were collected from Dharmapuri, Tamil Nadu. The ethanol extract was tested for hypoglycemic activity in normal rats. In oral glucose tolerance test, glucose (3 g/kg, p.o.) was administered to non diabetic control, metformin (250 mg/kg, p.o.) and DA extract (100 and 200 mg/kg, p.o.) to treat treated rats. Diabetes mellitus was induced by alloxan monohydrate (120 mg/kg, i.p.) in physiological saline after overnight fasting for 18 hours. DA extract (100 and 200 mg/kg, p.o.) and standard drug metformin (250 mg/kg, p.o.) were administered to diabetic rats for 21 days. Fasting blood glucose level and changes in body weight were measured on days 0, 7, 14, and 21. At the end of 21(st) day, serum lipid profile, total protein, albumin, and creatinine were assessed. RESULTS: In glucose loaded normal rats, the treatment with the extract of DA had shown a highly significant reduction (P < 0.001) in blood glucose levels at the doses of 100 and 200 mg/kg, respectively. The extract did not produce hypoglycemic activity at both the dose levels in normal, fasted rats. In alloxan induced diabetic rats, the body weight of the DA extract treated animals had shown a significant increase (P < 0.001) after 21 days treatment. The blood glucose level was reduced significantly by 47.48% and 52.09% after 21 days treatment at dose levels 100 and 200 mg/kg, respectively. Serum lipid levels, total protein, albumin, and creatinine were reversed toward near normal in treated rats as compared to diabetic control. CONCLUSION: The results indicate that ethanol extract of DA tubers possesses significant antidiabetic activity.